JADID DRAMAS AND THEIR ETHNOCULTURAL VALUES (Uzbek Scholar Journal, 2023)
This article talks about the formation of national ideology and culture in the beginning of the 20th century, the introduction of modern ideas, the struggle to achieve freedom and to have a new school system.